1986
DOI: 10.1002/ps.2780170209
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of DDT residues into milk of the Indian buffalo, Bubalus bubalis (L.) after oral and dermal exposure

Abstract: Three groups of buffaloes were fed with 20, 100 and 400mg of p,p'-DDT in their daily rations. The DDT residues in the milk fat of the treated animals showed an initial rapid rise but soon attained a dose-dependent equilibrium. The transfer coefficient of DDT residues in milk at 'plateau' levels showed an average value of about 12%. Half-life values for the rate of decline of DDT residues during the post-dosing period were computed according to a two-open-compartment model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Archer (1976) indicated that the microorganisms present in dairy products could reduce DDT and DDE to DDD under anaerobic conditions. Earlier papers also encountered the existence of p,p'-DDD as a dominant metabolite, constituting more than 50 % of EDDT in Indian butter (Dhaliwal and Kalra, 1978;Kalra et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…Archer (1976) indicated that the microorganisms present in dairy products could reduce DDT and DDE to DDD under anaerobic conditions. Earlier papers also encountered the existence of p,p'-DDD as a dominant metabolite, constituting more than 50 % of EDDT in Indian butter (Dhaliwal and Kalra, 1978;Kalra et al, 1986).…”
Section: Resultsmentioning
confidence: 99%
“…However, the limiting value (which may be defined as the concentration of a pesticide in feed and fodder if fed to lactating animals daily, the likely residues in milk will be less than their MRL values and safe for human consumption) of a pesticide in feed can be derived on the basis of its legal permissible limit in milk and its rate of transference from feed to milk. Based on short-term feeding experiments on buffaloes, the transfer coefficients of HCH isomers and DDT (Kalra et al 1986;Kalra 1988, 1993). Using these values, the limiting values of different pesticides in feed were calculated.…”
Section: Residues In the Samplesmentioning
confidence: 99%
“…Although the level of contamination of pond waters in our studies is relatively much less, yet the presence of HCH and DDT residues in pond waters is a matter of concern because consumption of contaminated pond waters by milch animals may lead to accumulation of lipophilic DDT and HCH residues in the animal body which ultimately gets secreted in milk (Kalra et al 1986). However, chances of further accumulation of DDT and HCH in soil and water in Haryana do not seem to be high because of restrictions imposed on their use on agricultural crops with effect from early ninties in India.…”
Section: Bdl -Below Detectable Limit Figures In Parentheses Denote Nmentioning
confidence: 99%